2014
DOI: 10.1071/rd12384
|View full text |Cite
|
Sign up to set email alerts
|

PAPPA2 is increased in severe early onset pre-eclampsia and upregulated with hypoxia

Abstract: Abstract. Severe early onset pre-eclampsia is a serious pregnancy complication, believed to arise as a result of persistent placental hypoxia due to impaired placentation. Pregnancy-associated plasma protein A2 (PAPPA2) is very highly expressed in the placenta relative to all other tissues. There is some evidence that PAPPA2 mRNA and protein are increased in association with pre-eclampsia. The aim of the present study was to characterise the mRNA and protein expression, as well as localisation, of PAPPA2 in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 26 publications
4
31
2
Order By: Relevance
“…Pregnancy-associated plasma protein A2 (PAPPA2) was up-regulated 2.6-fold (P < 0.001). PAPPA2 protein is elevated in EO PE placenta (24) and maternal serum before PE onset (25) and expressed by first-trimester EVT in women and by invasive trophoblasts in mice (26). However, the functional role of PAPPA2 in EVT invasion is not known.…”
Section: Il11 Impedes Human Evt Invasion Via the Pregnancy-associatedmentioning
confidence: 99%
“…Pregnancy-associated plasma protein A2 (PAPPA2) was up-regulated 2.6-fold (P < 0.001). PAPPA2 protein is elevated in EO PE placenta (24) and maternal serum before PE onset (25) and expressed by first-trimester EVT in women and by invasive trophoblasts in mice (26). However, the functional role of PAPPA2 in EVT invasion is not known.…”
Section: Il11 Impedes Human Evt Invasion Via the Pregnancy-associatedmentioning
confidence: 99%
“…Previous work reported that abnormal expression of PAPPA2 was associated with pregnancy complications (Buimer et al, 2008;Crosley et al, 2014a;Macintire et al, 2014;Munnangi et al, 2014). Circulating PAPPA2 was recommend as a valuable marker to screen early onset severe PE (Crosley et al, 2014b;Macintire et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating PAPPA2 was recommend as a valuable marker to screen early onset severe PE (Crosley et al, 2014b;Macintire et al, 2014). PE is typically characterized by insufficient EVT differentiation and inadequate maternal environment remodeling (Lyall et al, 2013) due to the impaired invasion and migration ability of EVT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations